2011
DOI: 10.1074/jbc.m110.169862
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Catalysis of Acylaminoacyl Peptidase

Abstract: Acylaminoacyl peptidase from Aeropyrum pernix is a homodimer that belongs to the prolyl oligopeptidase family. The monomer subunit is composed of one hydrolase and one propeller domain. Previous crystal structure determinations revealed that the propeller domain obstructed the access of substrate to the active site of both subunits. Here we investigated the structure and the kinetics of two mutant enzymes in which the aspartic acid of the catalytic triad was changed to alanine or asparagine. Using different su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…At last, the results from our simulations, where also the wild type ApAAP open and closed conformations are compared, strongly confirm the mechanism proposed in the literature of a “clamshell-like” conformational rearrangement at the interdomain interface in the proximity of the catalytic site, recently proposed [33]. In this context, the study of correlated motions and the networks of electrostatic interactions at the interface in both open and closed ApAAP conformations on ns time scales, allows to disclose relevant interactions and couple motions which can contribute to the transition between the two forms and which deserve further attention.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At last, the results from our simulations, where also the wild type ApAAP open and closed conformations are compared, strongly confirm the mechanism proposed in the literature of a “clamshell-like” conformational rearrangement at the interdomain interface in the proximity of the catalytic site, recently proposed [33]. In this context, the study of correlated motions and the networks of electrostatic interactions at the interface in both open and closed ApAAP conformations on ns time scales, allows to disclose relevant interactions and couple motions which can contribute to the transition between the two forms and which deserve further attention.…”
Section: Discussionsupporting
confidence: 89%
“…The switch between these two conformational states is likely to be mediated by modification of intermolecular interactions between the two domains and relying on the hinge role of D376 [33]. A similar conformation has been also identified by electron microscopy investigation of a POP enzyme [54].…”
Section: Resultsmentioning
confidence: 69%
“…In AAP enzymes, two different mechanisms for substrate screening have been proposed. Dimeric AAP (ApAAP) from Aeropyrum pernix shows dynamic opening and closing of the enzyme that are rather similar to observations in prokaryotic POPs and OPBs (25). In contrast, hexameric PhAAP shows the double-gated entry mechanism.…”
Section: Carboxypeptidase In Pop Family: Unique Enzyme Mechanismmentioning
confidence: 68%
“…Experimental studies demonstrated instead that isolated, unclosed β-propellers can be stable and suggested that enzyme activity relies rather on concerted movements of the peptidase and propeller domains [16], [17]. Nowadays a clamshell-like movement has been proposed to describe the substrate-induced conformational changes performed by several prolyl peptidases [18], [19], although analysis of molecular dynamics reveals that such conformational changes can be strikingly different in different enzymes, leading to different selectivity towards the substrate [20].…”
Section: Introductionmentioning
confidence: 99%